Strategies for maintaining communal harmony - Mathur, S.P. (2003)
Communal Harmony, construed basically as Hindu-Muslims amity, in Indian context, is mandated by all right thinking people, for not merely socio-politico-legal reasons but even for economic developmental and national security, as well. Experience has wisened us that mere law enforcement approach, basically involving management of resources by police, hardly prevents instances of communal violence and at best does damage control work. A strategic management and multi-disciplinary approach involving the state, its various organs, and the civil society at large, besides criminal justice administration alone can address the complex issue of communal harmony. - Reproduced.
Keywords: Communalism